2020
DOI: 10.1093/jxb/eraa363
|View full text |Cite
|
Sign up to set email alerts
|

The basic helix-loop-helix transcription factor bHLH95 affects fruit ripening and multiple metabolisms in tomato

Abstract: Ethylene signaling pathways regulate several physiological alterations that occur during tomato fruit ripening, such as changes in colour and flavour. However, the mechanisms underlying the transcriptional regulation of genes in these pathways remain unclear, although the role of RIN has been widely reported. In this report, we describe a bHLH transcription factor SlbHLH95, whose transcripts accumulated abundantly in breaker+4 and breaker+7 fruits compared to rin (ripening inhibitor) and Nr (never ripe). Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Among these genes, 13 members of the bHLH gene family and 12 members of the GRAS family undergo significant changes in their transcript levels during the early stages of ripening ( Figure 1D; Supplemental Table S1 ). This observation is in line with the reported downregulation of SlbHLH95 that affects accumulation of total carotenoids, lycopene, as well as ethylene sensitivity ( Zhang et al, 2020 ). Likewise, silencing of SlGRAS38 results in lower lycopene content and reduced ethylene production in tomato fruit, while the overexpression of SlGRAS4 leads to premature ripening ( Liu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Among these genes, 13 members of the bHLH gene family and 12 members of the GRAS family undergo significant changes in their transcript levels during the early stages of ripening ( Figure 1D; Supplemental Table S1 ). This observation is in line with the reported downregulation of SlbHLH95 that affects accumulation of total carotenoids, lycopene, as well as ethylene sensitivity ( Zhang et al, 2020 ). Likewise, silencing of SlGRAS38 results in lower lycopene content and reduced ethylene production in tomato fruit, while the overexpression of SlGRAS4 leads to premature ripening ( Liu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…More importantly, there was a positive correlation between the expression level of Cla017389 and the contents of lycopene (r =0.85), as mentioned above. The transcription factor bHLH is related to the carotenoid metabolism in tomato [34], papaya [35], and citrus [36]. In this study, the expression of Cla006599 and Cla022119 (bHLH) were decreased at 20 and 34 DAP as compared to 10 DAP, and their expression patterns were similar to CpbHLH1/2 that regulate carotenoid biosynthesis in papaya [35] (Additional le 2: Fig.…”
Section: Identi Cation Of Differentially Expressed Genes In Ve Genotypesmentioning
confidence: 60%
“…2). SlbHLH95 also was proved to be participated in the regulation of fruit ripening through ethylene metabolism pathway (Zhang et al 2020). In addition, co-expression network analysis found that several transcription factors including NAC, WRKY and bHLH showed co-expression relationship with VvUFD1 genes, suggesting they might be regulators of the expression of the VvUFD1 genes (Fig.…”
Section: The Vvufd1 Genes Might Play Roles In Fruit Development and Ripeningmentioning
confidence: 99%